Radiographic signs associated with damage to inferior alveolar nerve: A diagnostic tool to perform coronectomy - P T Gaikwad; A N Datarkar; R M Borle; R R Bonde; K C Vaidya; Ranjit Patil (Wolters Kluwer Medknow Publications, 2011)
Radiographic signs in the OPG, that indicate a relationship between the lower third molar and the inferior alveolar canal, are considered a risk factor for nerve damage- These signs are darkening of root, deflection of root, narrowing of root, bifid root apex, diversion of canal, narrowing of canal, interruption of white line of canal. The present study assesses the radiographic signs that indicate a relationship between the lower third molar and the inferior alveolar canal and application of these diagnostic tools for efficacy of coronectomy (intentional root retention) over the conventional technique of third molar removal in avoiding injury to the IAN. Eighty patients with radiographic features suggestive of close proximity of IAN to the roots were selected and were randomly divided into two equal groups. Group I patients underwent coronectomies and group I patients underwent removal of the lower third molars by conventional technique. Postoperative neurological assessment was carried out at regular intervals on day 1, 10th day, 1 and 3 months. In group I, none of the patients had evidence of inferior alveolar nerve injury, whereas, there was altered labial sensation in eight patients in group II.